The Duty to Produce One’s Firearm for Inspection in Terms of the Firearms Control Act: The Right to Silence under Siege? - Msaule, Phindile Raymond (Potchefstroom Electronic Law Journal, 2018)
The right of the arrested and accused persons to remain silent at pre-trial and during their trial are significant to ensuring a fair trial. The purpose of the right to remain silent is to ensure that the state bears the duty to prove the guilt of the accused beyond reasonable doubt. In essence, the right serves to dissuade the state from engaging in any manner or form of coercing the accused person to assist the state in meeting its case, whether during pre-trial or during trial. An individual who is accused of committing an offence must not through his or her words or deeds assist the state in satisfying its burden of proof. The Firearm Control Act 20 of 2000 (the Act) seems to dilute these rights. The Act empowers the police official to request an owner of a legal firearm to produce it within seven days of the request at a threat of a criminal sanction. At the time the request is made the individual has been neither arrested for nor accused of a criminal offence. However, on the failure to produce the firearm on demand by a police official the individual may be charged with a criminal offence and evidence that has been obtained in terms of the Act would be admissible at the subsequent trial. This is despite the fact that at the time the request to produce a firearm is made the individual does not have a choice but to comply with the request lest he or she be charged with an offence under the Act. The purpose of this contribution is to investigate whether the individual to whom a request to produce a firearm has been made is entitled to the right to remain silent entrenched in section 35 of the Constitution, and whether the limitation of this right by the Act passes constitutional muster.